Application of Whole-Cell Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry for Rapid Identification and Clustering Analysis of Pantoea Species - Rezzonico, Fabio (American Society for Microbiology (ASM), 2010)
Pantoea agglomerans is an ecologically diverse taxon that includes commercially important plant-beneficial strains and opportunistic clinical isolates. Standard biochemical identification methods in diagnostic laboratories were repeatedly shown to run into false-positive identifications of P. agglomerans, a fact which is also reflected by the high number of 16S rRNA gene sequences in public databases that are incorrectly assigned to this species. More reliable methods for rapid identification are required to ascertain the prevalence of this species in clinical samples and to evaluate the biosafety of beneficial isolates. Whole-cell matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) methods and reference spectra (SuperSpectrum) were developed for accurate identification of P. agglomerans and related bacteria and used to detect differences in the protein profile within variants of the same strain, including a ribosomal point mutation conferring streptomycin resistance. MALDI-TOF MS-based clustering was shown to generally agree with classification based on gyrB sequencing, allowing rapid and reliable identification at the species level.